Management of Student Planning at PAUD Qur'an El Rahmah - Ela Susilawati; H.E. Mujahidin; Syamsul Rizal (al-Afkar, Journal For Islamic Studies, 2023)
All experts agree that education is important for the progress of a nation and state. The progress of a nation and state can be seen from the quality of education in that country. Planning education is very important for an educational institution, because planning education means planning for success. Student planning is very important to do at the beginning to start an educational plan in schools. In planning students, the first thing to do is planning for the acceptance of new students, by planning for the acceptance of new students, learning activities at school can continue, PPDB is the start that needs to be considered in student planning. Because this is the key to the implementation of the learning process in schools. after planning the next acceptance of new students is planning school curricular and co-curricular activities, planning all activities to be carried out in schools from the learning process to evaluating student learning outcomes, then finally planning student graduation. From all these concepts, the school can be said to be good because it already has good planning too. Management of Student Planning in PAUD Qu'an El-Rahmah is carried out almost the same as other formal institutions, PPDB at Qu'an El-Rahmah PAUD is open from January to June. The mechanism for accepting new students at PAUD Qur'an El-Rahmah is 100 percent from the zoning route, where they live close is the reason parents send their children to PAUD Qur'an El-Rahmah.